Interrogating the complex roles and regulation of Vibrio cholerae Seventh Pandemic Islands - O'Hara, Brendan. (Tufts University. Tisch Library., 2023)
Thesis (Ph.D.)--Tufts University, 2022-08.; Submitted to the Dept. of Molecular Microbiology.; Advisor: Wai-Leung Ng.; Committee: Andrew Camilli, Aimee Shen, and Ralph Isberg.; Keyword: Microbiology.